Myelination increases chemical energy support to the axon without modifying the basic physicochemical mechanism of nerve conduction. (December 2020) - Ravera, Silvia; Morelli, Alessandro Maria; Panfoli, Isabella
Abstract: The existence of different conductive patterns in unmyelinated and myelinated axons is uncertain. It seems that considering exclusively physical electrical phenomena may be an oversimplification. A novel interpretation of the mechanism of nerve conduction in myelinated nerves is proposed, to explain how the basic mechanism of nerve conduction has been adapted to myelinated conditions. The neurilemma would bear the voltage-gated channels and Na + /K + -ATPase in both unmyelinated and myelinated conditions, the only difference being the sheath wrapping it. The dramatic increase in conduction speed of the myelinated axons would essentially depend on an increment in ATP availability within the internode: myelin would be an aerobic ATP supplier to the axoplasm, through connexons. In fact, neurons rely on aerobic metabolism and on trophic support from oligodendrocytes, that do not normally duplicate after infancy in humans. Such comprehensive framework of nerve impulse propagation in axons may shed new light on the pathophysiology of nervous system disease in humans, seemingly strictly dependent on the viability of the pre-existing oligodendrocyte. Highlights: The role of myelin as an electrical insulator should be revised. Myelin sheath is a site of extramitochondrial aerobic metabolism. The ATP produced in myelin seems delivered to the axon through gap junctions. Myelin contribution to the axonal energy demand could explain the increase of conduction speed in the myelinated axon. This new model may shed new light on the pathophysiology of nervous system disease in humans.